NILAI-NILAI MORAL DALAM SERAT WEDHATAMA DAN PENDIDIKAN BUDI PEKERTI - Sutrisna Wibawa (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstrak: Moral Values in Serat Wedhatama and Moral Education. Moral valuesare the highest values with four main characteristics: responsibility, conscience,absolute obligation, and formality. They are also related to what should not bedone due to the values that have to be highly praised. The moral values in SeratWedhatama include, among others, simple life, affection, responsibility, consciencedevelopment, love to others, humbleness, not being proud, religious obedience byconforming to the religious rules and avoiding what is prohibited, good positionsthrough sincere work everywhere, wealth through hardwork, and knowledge thatother people can benefit from. Such values are absolute moral values that are fixedand formal in nature. Serat Wedhatama can be a main reference for the learning oflocal contents of the Javanese Language, Literature, and Culture because it containsmoral values that can be used a basis for moral education.Keywords: Serat Wedhatama, moral values